The Dynamic Identity: Analysis Of Gender Identity In Breakfast On Pluto By Patrick Mccabe - Paramita Ayuningtyas (Bina Nusantara University, 2011)
Article focused on gender identity in Breakfast on Pluto by Patrick McCabe. By using Stuart Hall’s concept of identity, the analysis showed that gender identity had the potential to be deconstructed, as shown by the identity transformation done by Patrick Braden. Positioning by other people and his own body happened to be barriers for his identity transformation. However, those barriers basically could not stop Patrick’s transformation to be a woman. Patrick had its own strategies in changing his gender identity, which were gender deconstruction, body decoration, and language. It can be concluded that Breakfast on Pluto offers a discourse of identity that is dynamic. Identity is a becoming process that will happen endlessly in human’s life.